The counterbalance of the adverse side effects of releasing agent on the properties of cementitious materials with nano-particles. (January 2022) - Muhammad, Fawad; Hou, Pengkun; Wang, Zheng; Zhou, Xiangming; Cheng, Xin
Abstract: Organic releasing agent (RA) has been widely used on concrete formwork during casting and structuring for good surface quality. However, the harmful side effects introduced by the organic RA on cement hydration would finally lead to decreased property gain of hardened cementitious materials at the surface. In this work, 5 wt % RA was added into cement paste/mortar to simulate its effects on cementitious materials at the superficial layer when applied to formwork. Moreover, nano-particles (nano-SiO2 and nano-TiO2 ) have been introduced into the RA for counterbalancing the adverse effects on cement hydration by taking advantage of cement hydration acceleration effects of nano-modification. Results showed that the incorporation of nanoparticles into RA could result in a good dispersion with ultra-sonication. The addition of 4 wt % NS and 16 wt % NT into RA can improve the compressive strength of mortar by 28.2% and 38.1%. Meanwhile, they decrease water absorption rate up to 41.9% and 46.2% to that of the control sample (mortar with RA). Hydration heat calorimetry results demonstrated that the reaction of RA-added cement can be accelerated by nanoparticles, resulting in the microstructure's enhanced compactness (MIP). This work shed light on the nano-modification of concrete surface in a comfortable, efficient, and economical way.